Occupational Mobility of Ethnic Migrants - Thomas K. Bauer; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 1999)
This paper studies occupational mobility of ethnic German migrants who have entered Germany since 1984. The empirical analysis suggests significant differences in the probability of downward occupational mobility by gender, immigration status, and schooling levels. In general, migrants with higher skill levels face sharper deteriorations in their relative labor market position at the time of immigration, but are also able to reach their original occupational status much faster than low-skilled immigrants.
Keywords: J61; J24; J62; 330; Immigration; ethnic Germans; human capital transferability; occupational mobility; job search; Aussiedler; Arbeitsmobilität; Qualifikation; Bildungsinvestition; Schätzung; Internationale Arbeitsmobilität; Deutschland